Antarctic archaeology - Zarankin, Andrés; Salerno, Melisa Anabella
Archaeology has enabled researchers to tell alternative stories about Antarctica. Material remains have the power to shed light on the lives of the people who were the first to visit and work in the region -including anonymous sealers. From the analysis of capitalist strategies, to the study of practices and experiences, and the addition of new sites to the conservation agenda, archaeology is forcing the revision of the dominant narratives surrounding the history of Antarctica. Fil: Zarankin, Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidade Federal Do Minas Gerais. Departamento de Sociología y Antropología; Brasil Fil: Salerno, Melisa Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina